Kajian Regimen Dosis Penggunaan Obat Asma pada Pasien Pediatri Rawat Inap di Bangsal Anak RSUP. Dr. M. Djamil Padang - Rahmi Yosmar; Meri Andani; Helmi Arifin (Jurnal Sains Farmasi & Klinis, 2015)
A study on dosage regimens of asthma medications in pediatric patients hospitalized at the pediatrics ward DR. M. Djamil Padang hospital has been carried out. The purpose of this study was to determine and compare the suitability of dosage regimen given to pediatric patients in the pediatrics ward of Dr. M. Djamil Padang hospital with the literature. This study was conducted retrospectively with consecutive sampling technique. Samples were obtained from medical records during 2013. The results showed that the appropriate dosage administration of asthma medication for the prednisone, Combivent® and ambroxol were 100%, salbutamol 75%, and theophylline 0%. On the other hand, the entire medications showed 100% suitability concerning the route of administration. While for the interval of administration, the study showed that dexamethasone, prednisone, salbutamol, theophylline and ambroxol were 100% appropriate, but Combivent® was lower at 95.24%. The study concludes that the dose and interval of administration are not in accordance with the literature, while the route of administration is considered to be in accordance with the literature.